Double-layered metamaterial-based resonator operating at millimetre wave for detection of dengue virus - Qureshi, Suhail Asghar (2022)
The interest in microwave technology for biological applications using metamaterial as sensing element is increasing due to strong electric field compared to traditional microwave sensors. The operation at millimetre-wave frequencies further enhances the field intensity leading to increased sensitivity, which can be used in the detection of the dengue virus and it can be vital in controlling the disease. The millimetre-wave metamaterial-based resonators are presented in this thesis to characterise blood’s dielectric properties in the case of the dengue virus. The correlation coefficient, t-test, and cross-correlation were applied on S11 phase responses. During measurements, tap water was used instead of blood, and methylated alcohol was added to the water to lower its permittivity, mimicking the dielectric response of infected blood. First, a single-layered design with an engraved space to hold blood samples is presented as a proof of concept for blood-sensing and the application of statistical models. This sensor showed a resonance shift of 0.22 GHz due to an 8 unit decrease in blood’s permittivity. In contrast, three (3) designs of two-layered sensors are proposed with replaceable sensing layers suitable for repeated measurements. Double-layered Sensor 1 showed resonance at 36.28 GHz for normal blood. The perturbation observed was 0.88 GHz when the blood’s permittivity was reduced by 8 units. Sensor 2 showed a resonance shift from 27.22 GHz to 29.82 GHz with the 8 unit change in blood’s permittivity. Sensor 3 showed a lesser resonance shift, which is 0.44 GHz. However, the double-layered Sensor 3 has the edge over other designs in terms of its performance in all statistical methods. In double-layered sensors, the replaceable sensing layer provides quick and accurate results. As a result, the sensors presented here can detect the dengue virus using a simple finger-prick blood extraction method.